Criptovalute e Chiesa cattolica: prime riflessioni tra rischi e opportunità - Gravino, Federico (La moneta di Dio, 2022)
The technological revolution has involved the Catholic Church in the exercise of its functions. This interaction opens up new profiles also in the economic field through the introduction of crypto-alternative currencies. The opportunities and risks of the system of virtual currency circulation, the advantages and disadvantages connected to it, question its compatibility with the models of Catholic economic ethics and environmental sustainability.